Análise das percepções de segurança com eletricidade dos trabalhadores da cidade de Abaetetuba-PA - FONSECA, Alessandro de Araújo (2024)
This work aims to analyze the perception of electricity safety among workers in the city of Abaetetuba-Pará, using the safety measures described in NR-10 as a parameter. The research arises from the need to understand working conditions in the municipality's electrical sector, given the persistence of accidents of electrical origin in the country, despite the regulations in force in Brazil. To this end, a questionnaire was developed consisting of twelve questions that explored concepts related to measures to control and prevent electrical accidents. The research involved the participation of thirty professionals, the interviews took place in person and also online via the Whatsapp application. The participants were chosen based on contacts known to the author, with expansion through recommendations from these professionals and also in person visits to workplaces complemented the selection. After data analysis, it was observed that the majority of participants are young people, who have technical knowledge in the area, obtained through a professional course, technical course or practice. And they have an average professional experience of around 10 years. The professionals demonstrated that they followed the main parameters of NR-10, such as the use of PPE and the non-use of adornments during professional activities. Another point analyzed was the competence of these professionals when dealing with first aid situations or fires related to electricity. A significant number of interviewees admitted that they did not have adequate skills to intervene in these circumstances, going against the requirements of NR-10. Finally, the need for professionals to seek qualification in the area was identified, through professional, technical or even higher education courses, such as NR-10 training and recycling. This initiative aims to improve safety conditions and reduce the risk of accidents at work.